Improved survival of left ventricular assist device carriers in Europe according to implantation eras: results from the PCHF‐VAD registry. (24th May 2022) - Jakus, Nina; Brugts, Jasper J.; Claggett, Brian; Timmermans, Philippe; Pouleur, Anne‐Catherine; Rubiś, Pawel; Van Craenenbroeck, Emeline M.; Gaizauskas, Edvinas; Barge‐Caballero, Eduardo; Paolillo, Stefania; Grundmann, Sebastian; D'Amario, Domenico; et al.
Abstract : Aims: Temporal changes in patient selection and major technological developments have occurred in the field of left ventricular assist devices (LVADs), yet analyses depicting this trend are lacking for Europe. We describe the advances of European LVAD programmes from the PCHF‐VAD registry across device implantation eras. Methods and results: Of 583 patients from 13 European centres in the registry, 556 patients (mean age 53 ± 12 years, 82% male) were eligible for this analysis. Patients were divided into eras (E) by date of LVAD implantation: E1 from December 2006 to December 2012 (6 years), E2 from January 2013 to January 2020 (7 years). Patients implanted more recently were older with more comorbidities, but less acutely ill. Receiving an LVAD in E2 was associated with improved 1‐year survival in adjusted analysis (hazard ratio [HR] 0.58, 95% confidence interval [CI] 0.35–0.98; p  = 0.043). LVAD implantation in E2 was associated with a significantly lower chance of heart transplantation (adjusted HR 0.40, 95% CI 0.23–0.67; p  = 0.001), and lower risk of LVAD‐related infections (adjusted HR 0.64, 95% CI 0.43–0.95; p  = 0.027), both in unadjusted and adjusted analyses. The adjusted risk of haemocompatibility‐related events decreased (HR 0.60, 95% CI 0.39–0.91; p  = 0.016), while heart failure‐related events increased in E2 (HR 1.67, 95% CI 1.02–2.75; p  = 0.043). Conclusion: In an analysis depicting the evolving landscape of continuous‐flow LVAD carriers in Europe over 13 years, a trend towards better survival was seen in recent years, despite older recipients with more comorbidities, potentially attributable to increasing expertise of LVAD centres, improved patient selection and pump technology. However, a smaller chance of undergoing heart transplantation was noted in the second era, underscoring the relevance of improved outcomes on LVAD support. Abstract : Multiple factors influencing the outcomes of left ventricular assist device (LVAD) patients. BTT, bridge to transplantation; CIED, cardiac implantable electronic device; CRT, cardiac resynchronization therapy; DT, destination therapy; GDMT, guideline‐directed medical therapy; HMII, HeartMate II; HM3, HeartMate 3; HTx, heart transplantation; HVAD, HeartWare; ICD, implantable cardioverter‐defibrillator; MCS, mechanical circulatory support; RV, right ventricle.